Watching to Understand: How English-Dubbed Korean Films with Subtitles Affect Comprehension of Select Pupils - Abellana, Jupert Jasser G; Abellana, Marc Bryan (RIRAI Publisher, 2025)
The increasing popularity of Korean movies, especially those dubbed in English, has made a significant impact on Filipino television and viewers, particularly among pupils. This study aimed to explore the effects of English-dubbed Korean movies on the viewing comprehension of intermediate pupils. Specifically, it sought to assess the level of viewing comprehension, identify the positive and negative effects of Korean movies, and examine the cultural elements these movies present and their influence on comprehension. The researchers employed a Descriptive-Correlation design which surveyed 20 intermediate pupils who were shown three different genres of English-dubbed Korean movies. Following the screenings, the students completed a movie analysis questionnaire. The data were analyzed using Frequency and Percentages, as well as Chi-Square statistical tests to determine any significant relationships. The findings revealed that the socio-economic profiles of the respondents did not significantly relate to their viewing comprehension levels. Additionally, there was no significant correlation between the movie genres and the pupils' comprehension. The study recommends allowing sufficient time for further testing and suggests utilizing the private high school’s Audio-Visual Room to minimize distractions and enhance the viewing experience. This study contributes to the growing body of literature on media and education by highlighting how popular media, specifically English-dubbed Korean films, can serve as a tool for engaging students in language development and comprehension activities.